Sistem Informasi Manajemen Penelitian dan Pengabdian kepada Masyarakat di LPPM Universitas Timor Berbasis Web - Risald, Risald; Baso, Budiman (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2025)
This study discusses the development of the Research and Community Service Management Information System (Simpeka) at the Institute for Research and Community Service (LPPM) of the University of Timor to optimize the submission process for research and community service proposals. This web-based system was developed using PHP 5.6, MySQL 5.7, HTML5, CSS3, and JavaScript ES6. Testing involved the LPPM and relevant stakeholders to ensure the system met user requirements. The implementation results show an increase in the number of proposals from 150 in 2023 to 169 in the current year (an increase of 12.67%), a reduction in the average review time from 14 days to 7 days (50% efficiency), and a decrease in funding validation time from 7 days to 2 days (71.4% efficiency). The percentage of proposals validated according to the budget increased from 80% to 95% (an accuracy improvement of 18.75%). Technically, the Simpeka dashboard has an average load time of 1.8 seconds and a database query response time of 0.35 seconds. These improvements demonstrate that Simpeka can accelerate administrative processes, enhance transparency, and strengthen accountability in the management of research and community service at the University of Timor